THE CONCEPT OF LEADERSHIP JUSTICE IN THE QUR’AN: AN ANALYSIS OF IBN ‘ĀSHŪR’S MAQĀṢID AL-QUR’ĀN - Mohammad Alfin Niam; Nurbaiati; Nurcholik Achmad (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2026)
This article analyzes the concept of leadership justice in the Qur’an through Ibn ‘Āshūr’s maqāṣid al-Qur’ān approach. The main focus of this study is to examine how the value of justice is emphasized in three key verses, namely QS. al-Nisā’ [4]: 58, QS. Ṣād [38]: 26, and QS. al-Baqarah [2]: 124, and how these verses are understood through Qur’anic objectives such as tahdhīb al-akhlāq, siyāsat al-ummah, al-tashrī‘, and iṣlāḥ al-i‘tiqād. This study employs a qualitative library research method with a thematic-maqāṣidī analysis to identify the multilayered structure of meaning in leadership justice, encompassing moral, political, legal, and theological dimensions. The findings show that the Qur’an constructs the concept of just leadership through three main principles: trustworthiness, objectivity in judgment, and the prohibition of following personal desire. The maqāṣid approach reveals that leadership justice is not merely an ethical demand, but a Qur’anic objective aimed at establishing social stability, political integrity, and the moral maturity of society. This study affirms that leadership justice serves as a foundation of civilization and a key instrument for preventing social disorder and the abuse of power.